2014
DOI: 10.1038/srep04326
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ultra-sound during tape peeling

Abstract: We investigate the generation of the screeching sound commonly heard during tape peeling using synchronised high-speed video and audio acquisition. We determine the peak frequencies in the audio spectrum and, in addition to a peak frequency at the upper end of the audible range (around 20 kHz), we find an unexpected strong sound with a high-frequency far above the audible range, typically around 50 kHz. Using the corresponding video data, the origins of the key frequencies are confirmed as being due to the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…We show that the microstick-slip dynamics of the detachment front, due to the high-frequency periodic propagation of transverse fractures, can be observed (i) for imposed peeling velocities in the macroscopic stickslip domain, during the slip phase of the macroscopic instability, but also, (ii) for imposed peeling velocities in a finite range beyond the macroscopic stick-slip domain, where the peeling is rapid and regular at the macroscopic scale. In the former case, we confirm here the entanglement of the microscopic and macroscopic dynamical instabilities leading to a complex multi-scale stick-slip dynamics [16,18]. In contrast with the macroscopic stick-slip, we find that the highfrequency micro-stick-slip has an amplitude and a period independent of the peeled tape length L between the detachment front and the point at which the traction is applied.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…We show that the microstick-slip dynamics of the detachment front, due to the high-frequency periodic propagation of transverse fractures, can be observed (i) for imposed peeling velocities in the macroscopic stickslip domain, during the slip phase of the macroscopic instability, but also, (ii) for imposed peeling velocities in a finite range beyond the macroscopic stick-slip domain, where the peeling is rapid and regular at the macroscopic scale. In the former case, we confirm here the entanglement of the microscopic and macroscopic dynamical instabilities leading to a complex multi-scale stick-slip dynamics [16,18]. In contrast with the macroscopic stick-slip, we find that the highfrequency micro-stick-slip has an amplitude and a period independent of the peeled tape length L between the detachment front and the point at which the traction is applied.…”
supporting
confidence: 62%
“…Consequently, the micro-stick-slip period scales as T mss = A mss /v m (dashed line in Fig. 3) [18]. Thoroddsen et al [16] found a larger constant value, probably due to the different adhesive-substrate joint studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the rapid slip phases, the dynamical mode of failure is likely to give rise to small scale spatiotemporal front instabilities [16]. Indeed, ultrafast imaging could unveil that the peel front locally advances by steps in the main peel direction as a result of the propagation of a dynamic fracture kink in the transverse direction, at spatiotemporal scales much smaller than the macroscopic stick-slip [17][18][19]: the kink occurs periodically at ultrasonic frequencies with an amplitude of a few hundred microns, not only during the slip phase of the macro-instability, but also, for imposed peel velocities in a finite range beyond the macro-stick-slip domain where the peeling is regular at macroscopic scales [19].Interestingly, this micro-instability of the peel front characterized by the side-ways propagation of fracture kinks share similarities with other physical processes, as for instance the local con-tact lines dynamics on textured surfaces [20], or the dislocations motion in the yielding of crystalline materials [21]. While it was shown that those transverse cracks are accompanied by cycles of load and release of the elastic bending energy stored in the tape backing in the vicinity of the peel front [19], the physical origin of the micro-instability and its interaction with the macroscopic one remains an open issue.In this Letter, we provide a detailed experimental study of this micro-instability, varying systematically the peeled length L, the peel angle θ, the lineic mass µ and bending modulus B of the ribbon, over a wide range of driving peel velocities V .…”
mentioning
confidence: 99%
“…Solid friction behavior, specifically stick-slip motion [1][2][3][4][5][6][7][8], describes a wide range of physical phenomena encountered in daily life. It describes the squeaking of chalk on a chalkboard and the squealing of sand compressed underfoot on a beach [2], as well as low frequency rumblings of a fault shift during earthquakes [3].…”
Section: Introductionmentioning
confidence: 99%